La participación de los cirujanos novohispanos en las operaciones vacunales antes, durante y después de la “Real Expedición Filantrópica de la Vacuna” - Ramírez Ortega, Verónica; Rodríguez-Sala, María Luisa (Revista Complutense de Historia de América, 2010)
Small pox epidemics were among the most important ailments in the American populations of the Viceroyal period. This article analyses how the authorities and medical doctors of New Spain confronted the epidemics. The diffusion of Edward Jenner’s vaccine took place at an early stage in this territory, and its application was carried out in two phases. The first phase was carried out during the early years of the 19th century by local doctors, and the second, by the doctors and the members of the Royal Philanthropic Expedition in 1804. Both efforts were initiated independently, but came to complement each other and even joined hands in order to spread the vaccine against Small Pox throughout the kingdom of New Spain and procure its conservation for future use.
Keywords: Surgeons; Smallpox; Vaccine; Expedition; Medicine; New Spain; 19th Century